Pemberdayaan Masyarakat Lokal Berbasis Potensi Wisata Dusun Pelanjau Desa Bukit Segoler Kecamatan Tebas Kabupaten Sambas - Asbeni; Nurchalis; Yustia Amelia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Dusun Pelanjau of Bukit Sigoler Village, has a variety of local potentials that can be developed into tourism potential, to optimize the existing potential, there is a need for community empowerment efforts to optimize the tourism potential of dusun Pelanjau in order to improve the welfare of its people. This study aims to determine the empowerment of local communities based on the tourism potential of the dusun Pelanjau of Bukit Sigoler. The method used in this study is a qualitative method with purposive sampling technique. Data collection techniques were carried out by observation, interviews, and documentation. The results of this study indicate that dusun Pelanjau has a lot of potential that can be developed into tourism potential such as customs, historical sites and nature. This potential is a supporting factor and the community is an inhibiting factor because people do not know much about tourism. The community empowerment process is carried out by raising awareness in the form of conducting socialization, skills skills where the government can provide training to Pokdarwis and the community and increasing intellectual abilities or institutional strength where at this stage the government has formed Pokdarwis through a decree from the local government and includes the Pokdarwis program. into the village budget.